2021
DOI: 10.1371/journal.pone.0246817
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphological and connectivity changes on MRI after stem cell therapy in a rat stroke model

Abstract: In animal models of stroke, behavioral assessments could be complemented by a variety of neuroimaging studies to correlate them with recovery and better understand mechanisms of improvement after stem cell therapy. We evaluated morphological and connectivity changes after treatment with human mesenchymal stem cells (hMSCs) in a rat stroke model, through quantitative measurement of T2-weighted images and diffusion tensor imaging (DTI). Transient middle cerebral artery occlusion rats randomly received PBS (PBS-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In the present study, DTI images showed that decreased FA values in the sensorimotor cortex and internal capsule of the ischemic hemisphere after ischemia, while TSTT treatment significantly elevated FA value in the corresponding areas. In general, the decreased FA value is possibly attributed to structural breakdown of axons, but enhanced FA represents axonal remodeling after stroke (Son et al, 2021). Data herein indicated that TSTT might facilitate microstructural integrity after ischemic stroke.…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, DTI images showed that decreased FA values in the sensorimotor cortex and internal capsule of the ischemic hemisphere after ischemia, while TSTT treatment significantly elevated FA value in the corresponding areas. In general, the decreased FA value is possibly attributed to structural breakdown of axons, but enhanced FA represents axonal remodeling after stroke (Son et al, 2021). Data herein indicated that TSTT might facilitate microstructural integrity after ischemic stroke.…”
Section: Discussionmentioning
confidence: 67%
“…To construct an accurate animal head model, a numerical simulation model of the animal was created by digitizing the animal head structure using 7.0 T MRI 19 . The coil developed by this research team was applied to an animal head model to measure the actual magnetic field value, and the conditions for applying the voltage under the same conditions as those of the clinical study were traced.…”
Section: Discussionmentioning
confidence: 99%
“…A quadrature birdcage coil (inner diameter, 72 mm) was used for excitation, and an actively decoupled 4-channel phased array surface coil was used to receive the signal. T2-weighted images were acquired from C57BL/6N mice under isoflurane anesthesia (5% for induction, 1.5% for maintenance) using a turbo rapid acquisition with refocusing echoes (Turbo RARE) sequence with the following parameters: repetition time (TR)/echo time (TE) = 3000/60 ms; number of averages = 4; field of view = 30 × 30 mm 2 ; image matrix = 192 × 192; and in-plane resolution = 0.156 × 0.156 × 0.75 mm 3 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Compared to CT scans, MRIs are more effective at exposing subtle differences between soft tissues, nerves and blood vessels. Using MRI can detect flowing blood and puzzling vascular malformations as well as demyelination disease without beam-hardening artifacts and any ionizing radiation (8,9). Compared to PET, MRI completes one scan faster with a temporal resolution of ~3 seconds (9)(10)(11).…”
Section: Overview Of Mri In Diagnosis Of Cvdsmentioning
confidence: 99%